Evaluation of Student Applications Made for Psychological Reasons to a University Hospital Health Center - Mustafa Cankurtaran; Hilal Aksoy; İzzet Fidancı; Umut Ulusu; Seval Tunç; Duygu Ayhan Başer (Genel Tıp Dergisi)
Objective: With this study, it was aimed to determine the reasons and results of young adults who apply with psychological problems in a primary care institution of a university and to evaluate the relationship between sociodemographic characteristics. Method: The descriptive and retrospective study was conducted in Hacettepe University Faculty of Medicine, Department of Family Medicine and Sıhhiye Health Center. All students between the ages of 18-35, who were registered in the specified date range in our study, and who came to a psychologist interview at least 3 times at regular intervals were evaluated. In our study, the data of the patients were collected by examining the data forms recorded by the psychologist. The personal data of the patient was not used in the data form. Results: In the study, 276 applications were evaluated retrospectively. It was observed that 83.3% of the applicants were women, and the mean age was 20.99±2.176. When evaluated in terms of application reasons; it was determined that 35.5% of them applied due to anxiety, stress, obsessive-compulsive disorder [OCD] problems, 35.9% of them had communication problems and psychosocial problems. For the treatment of 65.2%, it was decided to follow up with a psychologist [who did not require referral to a psychiatrist]. When the relationship between the outcome of the applications and the reasons for the application is evaluated; 54.8% of mood problems were referred to a psychiatrist and were followed up by a psychologist after the medication was started; it was determined that 51.1% of the patients who applied with communication and psychosocial problems were followed up by a psychologist without the need for referral to a psychiatrist. Conclusion: As a result, university students have high levels of anxiety, stress, OCD problems, communication problems, and psychosocial problems; it was found that women, those living in dormitories and those with a diagnosis of psychiatric illness applied more frequently. Students should be encouraged to benefit from the health centers, which are created for them, where primary care preventive health care is at the forefront.